188 Senior clinical and business managers'perspectives on how different mechanisms and models of employing general practitioners in or alongside Emergency Departments influence wider system outcomes. Issue 12 (23rd November 2020) - Choudrhey, Mazhar; Edwards, Michelle; Cooper, Alison; Anderson, Pippa; Hughes, Thomas; Carson-Stevens, Andrew; Porter, Alison; Adrian, Edwards
Abstract : Aims/Objectives/Background: We aim to examine senior managers' perspectives on funding mechanisms used to implement the policy and experiences of success or challenges in introducing models of using GPs in or alongside emergency departments. Health policy in England has advocated the use of primary care clinicians at emergency departments to address pressures from rising attendances. However, implementing large systemic changes such as placing GPs in or alongside emergency departments requires significant funding, consideration of the opportunity costs of the alternative uses of such funding, an available workforce and evidence of how it should be used. Our findings will inform policy adaptation and service development to improve the healthcare provided to patients by providing new evidence of the reported experiences of adopting models of using GPs in or alongside emergency departments. Methods/Design: The perspectives of senior clinical, business and finance managers with responsibility for emergency department services and on-site primary care service implementation were investigated in semi-structured interviews with 31 managers at 12 type-1 emergency departments in England and Wales. Emergency departments operated one of three GP models or had prior experience of implementing a GP model. Interviews were thematically analysed. Results/Conclusions: Successful GPs models in emergency departments were perceived to be reliant on well-organised and unified funding mechanisms, appropriate staffing and governance, and consideration of population demands and needs. Funding mechanisms and the flow of funds were reported as complex, the most efficient mechanisms were described at departments where funding was unified, in collaboration with health and community care services. Staffing with local, experienced GPs was important. There were also cautions from experiences with private locum providers. Our findings contribute to debates about implementing policy on how primary care clinicians are effectively and safely deployed in emergency departments and how local context should be considered.